Pengaruh Komunikasi dan Kepuasan Kerja Terhadap Kinerja Pegawai Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Lampung Tengah - Aldila Rinaldo; Agus Wahyudi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of communication and job satisfaction on employee performance at the Regional Financial and Asset Management Agency of Central Lampung Regency. This research employed a quantitative approach using a survey method. The population consisted of all employees of BPKAD Central Lampung Regency, with a total of 41 respondents selected using a simple random sampling technique. Data were collected through questionnaires, while data analysis was conducted using multiple linear regression analysis with the assistance of SPSS software. Hypothesis testing was performed using t-tests, F-tests, and the coefficient of determination (R²). The results indicate that communication and job satisfaction partially have a positive and significant effect on employee performance. Simultaneously, communication and job satisfaction also have a positive and significant effect on employee performance. The coefficient of determination (R²) value of 0.803 indicates that 80.3% of the variation in employee performance can be explained by communication and job satisfaction, while the remaining percentage is influenced by other factors outside the research model. Job satisfaction is identified as the most dominant variable affecting employee performance. This study is expected to serve as a reference for improving employee performance in local government institutions.